Implementation Of Field Line Operational Strategies And Mechanisms In Business Management For Increasing Acceptor Family Income (UPPKA) In The City Of Bandung - Imbrani, Hari; Setiawan, Iwan; Yulia Wijaya, Dina (Universitas INABA, 2025)
The implementation of the acceptor family income increase business program (UPPKA) in the city of Bandung is a strategic effort to strengthen economic resilience and encourage family independence through the development of community-based business groups. This program is implemented systematically through four main stages, namely the collection of acceptor data in a measurable manner to ensure the accuracy of the target; implementation of periodic coaching and mentoring to improve family business skills and capacity; the implementation of a periodic reporting system to monitor the progress of the business; as well as the implementation of routine coordination between group management, cadres, and related agencies. The method used in the implementation of this activity is training and assistance so that it is right on target in implementing procedures and techniques for the program that has been determined. The results show that various activities such as business management training, technical assistance in the field, preparation of business reports, and cross-sector coordination have effectively increased family income, expanded business networks, and fostered entrepreneurial spirit. This success makes UPPKA a relevant model of sustainable family empowerment to be replicated in other regions with appropriate local adjustments.